Economic crisis management policy, practice, outcomes and prospects - Tran, Van Hoa.; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2002)
Economic Crisis Management discusses contemporary and economic policy and its application to major crisis economies in Asia. The book contains a collection of studies by international experts in economics and finance with special focus on major aspects of the economic management of the Asia crisis.
Machine generated contents note: 1 Economic Crisis Management: An Overview 1 -- Tran Van Hoa -- 2 Economic Management and Recent Financial Crises 6 -- Tran Van Hoa -- 3 Monetary and Fiscal Policy and Crisis Economies 14 -- J.O.N. Perkins -- 4 Economic Reforms and Constitutional Transition 28 -- Jeffrey Sachs, Wing Thye Woo and Xiaokai Yang -- 5 Thailand's Financial and Economic Crisis - Evaluating Alternative Policies for Economic Recovery 86 -- Wilai Auepiyachut and Charles Harvie -- 6 Financial Crisis Management in Korea: Processes and Consequences 112 -- Junggun Oh, Hyun-Hoon Lee and Charles Harvie -- 7 Vietnam: Economic and Financial Management 146 -- Tran Van Hoa and CIEM -- 8 The Philippines: Crises and Economic Crisis Management 167 -- Tran Van Hoa -- 9 Indonesia: Managing Economic and Social Collapse 183 -- Charles Harvie -- 10 Singapore: Economic Management During and After the Asia Crisis 220 -- Tran Van Hoa -- 11 Management of Economic and Financial Crises: Synthesis and the Road Ahead 238 -- Tran Van Hoa.
Includes bibliographical references and index.
Keywords: Financial crises -- Asia; Foreign exchange -- Asia; Monetary policy -- Asia; Asia -- Economic policy; Asia -- Economic conditions -- 1945-; Asia -- Foreign economic relations; Electronic books